PRAKTEK GADAI TANAH DI KECAMATAN CIBEUREUM DALAM PERSPEKTIF EKONOMI ISLAM - Sandi Mutia, Acep; Rahmat Nurhayat, Zaidan; Setiawan, Bambang (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The objective of this study is to identify the perspectives of three schools of thought regarding the implementation of the land pawn system. This research was conducted in Cibeureum District. The research approach used is qualitative. The study shows that although the Ijab Qobul is performed verbally in the local language, its implementation complies with Islamic law. Other aspects concerning the Rahin and Murtahin are also regulated under Islamic law, as both parties are considered mature, sane, and legally aware. In Islamic law, land is also considered a valid form of collateral, making the marhun legitimate. If the pawnee excessively utilizes the land, such actions are deemed inappropriate and invalid according to Islamic law. This is because it involves exploiting misfortune, which is unjust for the “Rahin” and entirely contradicts the principles of Muamala.